2021
DOI: 10.1186/s12610-021-00133-9
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of serum anti-Müllerian hormone in the management of azoospermia and the prediction of testicular sperm retrieval outcomes: a study of 155 adult men

Abstract: Background Testicular sperm extraction (TESE) is the method of choice for recovering spermatozoa in patients with azoospermia. However, the lack of reliable biomarkers makes it impossible to predict sperm retrieval outcomes at TESE. To date, little attention has been given to anti-Müllerian hormone (AMH) serum levels in adult men with altered spermatogenesis. In this study we aimed to investigate whether serum concentrations of AMH and the AMH to total testosterone ratio (AMH/T) might be predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 36 publications
1
14
0
1
Order By: Relevance
“…Among other factors, consideration of serum T levels and the functional status of the Sertoli cells are required. Consequently, using the ratio of AMH to total T (AMH/tT) may provide a potentially effective biomarker for predicting the severity of testicular failure, as previously suggested ( 11 , 12 ). However, the current lack of serum AMH reference ranges in normozoospermic adult men obscures the interpretation of such analyses.…”
mentioning
confidence: 95%
“…Among other factors, consideration of serum T levels and the functional status of the Sertoli cells are required. Consequently, using the ratio of AMH to total T (AMH/tT) may provide a potentially effective biomarker for predicting the severity of testicular failure, as previously suggested ( 11 , 12 ). However, the current lack of serum AMH reference ranges in normozoospermic adult men obscures the interpretation of such analyses.…”
mentioning
confidence: 95%
“…23 , 24 In a newly published study, Benderradji et al . 25 suggested that AMH serum levels were significantly lower in patients with unexplained NOA, and the lowest values were observed in patients with genetic NOA (compared with unexplained NOA), especially in individuals with nonmosaic KS.…”
Section: Discussionmentioning
confidence: 98%
“…In the adult male, serum AMH usefulness is more limited than that of the other typical Sertoli cell marker, inhibin B. Nonetheless, it has been proposed to contribute to the management of azoospermia and the prediction of testicular sperm retrieval [ 40 ].…”
Section: The Anti-müllerian Hormone Systemmentioning
confidence: 99%